2018
DOI: 10.1002/hbm.24061
|View full text |Cite
|
Sign up to set email alerts
|

The role of the right temporo–parietal junction in social decision‐making

Abstract: Identifying someone else's noncooperative intentions can prevent exploitation in social interactions. Hence, the inference of another person's mental state might be most pronounced in order to improve social decision-making. Here, we tested the hypothesis that brain regions associated with Theory of Mind (ToM), particularly the right temporo-parietal junction (rTPJ), show higher neural responses when interacting with a selfish person and that the rTPJ-activity as well as cooperative tendencies will change over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 92 publications
5
36
0
Order By: Relevance
“…The TPJ is involved in multiple cognitive functions (Alkire, Levitas, Warnell, & Redcay, ; Baumgartner, Dahinden, Gianotti, & Knoch, ; Donaldson et al, ; Fujino, Yamasaki, et al, ; Mars et al, ; Soutschek et al, ). In particular, the right TPJ plays a key role in social cognition, such as perspective taking (Krall et al, ; Schurz, Tholen, Perner, Mars, & Sallet, ; Tei et al, ), moral decision‐making (Bitsch, Berger, Nagels, Falkenberg, & Straube, ; Chen, Decety, Huang, Chen, & Cheng, ; Tei et al, , ; Young, Camprodon, Hauser, Pascual‐Leone, & Saxe, ), and strategic social behavior (Hampton, Bossaerts, & O'Doherty, ; Hill et al, ). Significantly, previous fMRI studies have shown that the right TPJ plays a vital role in differentiating between in‐group and out‐group members in judgments and behavior (Baumgartner et al, ; Falk et al, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The TPJ is involved in multiple cognitive functions (Alkire, Levitas, Warnell, & Redcay, ; Baumgartner, Dahinden, Gianotti, & Knoch, ; Donaldson et al, ; Fujino, Yamasaki, et al, ; Mars et al, ; Soutschek et al, ). In particular, the right TPJ plays a key role in social cognition, such as perspective taking (Krall et al, ; Schurz, Tholen, Perner, Mars, & Sallet, ; Tei et al, ), moral decision‐making (Bitsch, Berger, Nagels, Falkenberg, & Straube, ; Chen, Decety, Huang, Chen, & Cheng, ; Tei et al, , ; Young, Camprodon, Hauser, Pascual‐Leone, & Saxe, ), and strategic social behavior (Hampton, Bossaerts, & O'Doherty, ; Hill et al, ). Significantly, previous fMRI studies have shown that the right TPJ plays a vital role in differentiating between in‐group and out‐group members in judgments and behavior (Baumgartner et al, ; Falk et al, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the amygdala is an important brain region for emotion recognition [24,62] and has been shown to be involved in salience processing [28], further studies are needed to investigate the specific role of the amygdala in social decision making. In addition, to investigate the importance of different brain regions in social decision making more comprehensively, the presented social JTC-task might be analyzed with regard to the right temporoparietal junction and particularly its functional connectivity with the left hippocampus, which recently has been shown to be important for social decision making and social learning in the context of an iterated prisoner's dilemma game [63].…”
Section: Discussionmentioning
confidence: 99%
“…During creative cognition, neuroimaging findings reveal activity patterns in a widespread neural network involving brain regions related with cognitive control mechanisms such as the superior frontal gyrus (Hu et al, 2016), the inferior frontal gyrus (IFG, Beaty et al, 2014;Flaherty, 2005), the dorsolateral prefrontal cortex (dlPFC, Beaty et al, 2015;Flaherty, 2005) and brain regions associated with default mode processes such as the bilateral inferior parietal lobule (IPL), the posterior cingulate cortex (PCC), the medial prefrontal cortex (mPFC) and areas in the medial temporal lobe (MTL) such as the amygdala and the hippocampus, which are assumed to be critical for spontaneous and broadened thinking Bitsch et al, 2018b;Buckner et al, 2008). Humor production abilities have been found to have much in common with other forms of verbal creativity (Nusbaum et al, 2017;Perchtold-Stefan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%